2019
DOI: 10.1007/s10826-019-01502-9
|View full text |Cite
|
Sign up to set email alerts
|

Bullying, Peer Victimization, and Child and Adolescent Health: An Introduction to the Special Issue

Abstract: Significant health problems of adolescents involved in bullying has been documented in the research literature. Research consistently reports that youth who are involved in bullying are at a significant risk of health problems (e.g., depression, anxiety, sleeplessness). Likewise, those with health problems are at an increased odds of bullying and peer victimization. The Special Issue, "Bullying, Peer Victimization, and Child and Adolescent Health", of the Journal of Child and Family Studies brings together sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…Bullying can be seen everywhere, in any environment, at any age, and at any time; it is an increasingly serious problem that can affect every individual, regardless of its sociocultural structure (Hong et al, 2019). The prevalence of bullying worldwide varies between 8% and 70% (Menesini & Salmivalli, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bullying can be seen everywhere, in any environment, at any age, and at any time; it is an increasingly serious problem that can affect every individual, regardless of its sociocultural structure (Hong et al, 2019). The prevalence of bullying worldwide varies between 8% and 70% (Menesini & Salmivalli, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of bullying worldwide varies between 8% and 70% (Menesini & Salmivalli, 2017). Bullying in schools negatively affects the child physically, mentally, and socially, and these negative effects continue throughout the child's entire life (Evgin & Bayat, 2020; Hong et al, 2019). The family environment is one of the most important factors that ensure that a child develops into a healthy, happy, and independent individual (Totan & Yöndem, 2007; Yavuzer, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial covariation between bullying, victimization, a range of mental and physical health problems, and eating and weight concerns (Copeland et al, 2015; Hong, Espelage, & Rose, 2019; Wolke, Copeland, Angold, & Costello, 2013). General bullying intervention program evaluations (e.g., interventions that focus on reducing all forms of bullying and aggression, rather than focusing on weight stigma and/or eating disorders, more specifically) tend not to measure weight or appearance-related teasing and eating behaviors as outcomes of their intervention efforts.…”
Section: Discussionmentioning
confidence: 99%
“…They are also more likely to be lonely and to want to avoid school. Hong et al [49] reported that children and adolescents were at higher risk of anti-social behaviors such as problems at school, substance use, and aggressive behavior, which increase the chance of depression.…”
Section: Discussionmentioning
confidence: 99%